Soft Architecture: Walking as an Affective Practice in Lisa Robertson’s “Seven Walks” - MacPherson, Sandra (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
In Lisa Robertson’s “Seven Walks” the speaker and guide do not simply amble through Vancouver’s material space. Their walks are an affective practice that expresses the city in terms of the fluidity of becoming rather than the fluidity of commodity exchange and suggests that the productivity of sexually differentiated walking is distinct from traditional masculinist discourses of the peripatetic as contemplative or simply transgressive.